Physicochemical and antioxidant properties of pectin from Actinidia arguta Sieb.et Zucc (A. arguta) extracted by ultrasonic - Liu, Liqi; Sui, Yuhan; Wang, Tienan; Li, Xiang; Chen, Lina; Shi, Mao (Frontiers in Nutrition, 2024)
Pectin was extracted from Actinidia arguta Sieb. et Zucc (A.arguta) using the ultrasound-assisted acid method and the single acid method. The physicochemical properties, structure, and antioxidant properties of two different pectins were investigated. The results showed that the extraction yield of the ultrasound-assisted acid method is higher than that of the single acid method. The molecular structure of A. arguta pectin extracted by the ultrasound-assisted acid method belongs to a mixed structure of RG-I and HG-type domains. Through structural feature analysis, the ultrasound-assisted extraction pectin (UAP) has a more branched structure than the single acid-extracted pectin (SAP). The SAP has a higher degree of esterification than the UAP. The physical property results show that the viscosity, solubility, and water-holding capacity of the UAP are better than those of the SAP. The antioxidant test results show that the hydroxyl radical scavenging and reducing powers of the UAP are superior to those of the SAP. This study shows the composition, physicochemical properties, and antioxidant activity of A. arguta pectin extracted by the ultrasonic-assisted extraction method to provide a theoretical basis for its application as an antioxidant and other food additives in the food industry.